Baseline predictors of persistence to first disease‐modifying treatment in multiple sclerosis. (30th October 2016) - Zettl, U. K.; Schreiber, H.; Bauer‐Steinhusen, U.; Glaser, T.; Hechenbichler, K.; Hecker, M.
Abstract : Objectives: Patients with multiple sclerosis (MS) require lifelong therapy. However, success of disease‐modifying therapies is dependent on patients' persistence and adherence to treatment schedules. In the setting of a large multicenter observational study, we aimed at assessing multiple parameters for their predictive power with respect to discontinuation of therapy. Materials and methods: We analyzed 13 parameters to predict discontinuation of interferon beta‐1b treatment during a 2‐year follow‐up period based on data from 395 patients with MS who were treatment‐naïve at study onset. Besides clinical characteristics, patient‐related psychosocial outcomes were assessed as well. Results: Among patients without clinically relevant fatigue, males showed a higher persistence rate than females (80.3% vs 64.7%). Clinically relevant fatigue scores decreased the persistence rate in men and especially in women (71.4% and 51.2%). Besides gender and fatigue, univariable and multivariable analyses revealed further factors associated with interferon beta‐1b therapy discontinuation, namely lower quality of life, depressiveness, and higher relapse rate before therapy initiation, while higher education, living without a partner, and higher age improved persistence. Conclusions: Patients with higher grades of fatigue and depressiveness are at higher risk to prematurely discontinue MS treatment; especially, women suffering from fatigue have an increased discontinuation rate.